Sécurité sanitaire sous dépendance - Marie Coris; Alain Piveteau; Philippe Gorry; Matthieu Montalban (Revue de la Régulation)
Improving public health security on a sustainable basis is not simply a matter of adjusting economic variables or a few incentives, even on a large budgetary scale. Such an ambition implies that new compromises must be made at the different levels of stakeholders in health security. This is a new public policy challenge to which industrial policy must contribute independently of the traditional objective of improving competitiveness.We focus on the case of the drug industry to discuss this proposal. First, we note the emergence of a shortage of medicines in rich countries. This reflects the fragility of a globalized industry in the wake of the internationalization of patent protection in 1995. We then return to the national debate in France. The search for solutions to the production problem has focused on relocation or on improving competitiveness. But the debate has failed to understand the complexity of the determining factors in the location of pharmaceutical companies and to overcome the contradictions at work in this productive and security crisis. Finally, we consider the regional territory as one of the proper scales at which constructing a socio-productive compromise likely to support the objectives of a health security based on an industrial policy in need of major rethinking.